Taxonomy of Patience in Sixteenth-century Florentine Political Thought - Czapińska-Bambara, Marta (Studia Ceranea, 2024)
This article examines the concept of pazienza present in the writings of Machiavelli and Guicciardini. It turned out that it is closely related to key concepts for their considerations, such as Fortune, Time or Opportunity, and is classified and valued by them in social interaction within the political hierarchy. In Machiavelli, the term pazienza is an expression of patient enduring of an inconvenient situation, which should be assessed positively or negatively depending on who is patient and in what circumstances. In the context of social relations, Machiavelli perceives the effects of patience rather negatively, because for him it is mainly an expression of weakness, leading to or resulting from the loss of political position. For Guicciardini, patience means the ability to endure adversity, but also the ability to wait for the right moment to take action. Guicciardini emphasizes the ambivalent meaning of patience, which, on the one hand, is passive bearing of someone else’s will, and on the other, as an expression of understanding the situation, turns out to be necessary when concluding alliances, negotiations and conducting military activities, i.e. it is simply indispensable in socio-political life, because it promotes implementation of plans, but also limits the use of violence.